Characteristics of Successful Quality Improvement Teams: Lessons from Five Collaborative Projects in the VHA - Mills, Peter D.; Weeks, Bill (The Joint Commission Journal on Quality and Patient Safety, 2004)
Article-at-a-Glance Background A pre–post observational design was used to study the aggregate results of five national Breakthrough Series (BTS) collaboratives run within Veterans Health Administration (VHA) to identify the organizational, interpersonal, and systemic characteristics of successful improvement teams. Methods One hundred thirty-four medical quality improvement teams participated in five BTS collaboratives in the VHA between 1999 and 2002. Team characteristics were assessed using a team questionnaire before and after the BTS collaboratives. Results Fifty-seven percent of participating teams were rated as successful (a 20% improvement from baseline for at least two months before the collaboratives' end). More high-performing medical quality improvement teams perceived their work to be part of their organization's key strategic goals. By the end of the BTS collaboratives, high-performing teams had more front-line staff support and stronger team leadership. Discussion Strong organizational support, strong team leadership, and high levels of interpersonal team skills help medical quality improvement teams go further to improve clinical care. It is recommended that quality improvement teams become integrated with their organization's key strategic goals, that improvement teams stay together, and that leadership and team training be provided to improve clinical outcomes.